AGE-FRIENDLY AND DEMENTIA-FRIENDLY MASSACHUSETTS. (11th November 2018) - Bonner, A
Abstract: The Massachusetts Healthy Aging Collaborative (MHAC) is a group of more than 100 agencies and organizations committed to advancing healthy aging and age-friendly communities throughout the state. There are now 86 active or emerging age-friendly, over 54 active or emerging dementia-friendly communities and 76 Memory Cafes in MA. See the online map: mahealthyagingcollaborative.org/age-friendly/ma/map. In 2017, Governor Charles D. Baker established a Council to Address Aging in Massachusetts. The Council seeks to make MA the most livable state for people at every age. Efforts focus on: improving economic security; ensuring access and affordability of health and supportive services necessary to optimize independence; promoting age-friendly communities; facilitating connection and engagement. Cross-cutting themes include promoting access, equity, cultural competency and inclusion, as well as leveraging innovation and technology informing all recommendations. In 2018, MA became the second US state to have their application to become an age-friendly state approved by AARP.